1996
DOI: 10.1007/bf00195935
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic monitoring of nalbuphine: transplacental transfer and estimated pharmacokinetics in the neonate

Abstract: Nalbuphine, a mixed agonist-antagonist opiate, is commonly used as a systemic analgesic during labour. Recent reports of perinatal adverse effects prompted us to carry out therapeutic nalbuphine monitoring in obstetric analgesia. Because data on fetomaternal transfer are scarce and the pharmacokinetics of this drug in the neonate are largely unknown, we report data obtained from 28 parturients treated with nalbuphine either intramuscularly and/or intravenously during labour. Plasma nalbuphine levels were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Although nalbuphine has been approved for clinical use in children, pharmacokinetic data of the drug remain very limited. Nicolle and colleagues 7 reported data for a few neonates whose mothers had received nalbuphine during labour. Jacqz-Aigrain and colleagues 8 have reported data of a population pharmacokinetic study carried out in neonates.…”
Section: Accepted For Publication: 17 December 2010mentioning
confidence: 99%
“…Although nalbuphine has been approved for clinical use in children, pharmacokinetic data of the drug remain very limited. Nicolle and colleagues 7 reported data for a few neonates whose mothers had received nalbuphine during labour. Jacqz-Aigrain and colleagues 8 have reported data of a population pharmacokinetic study carried out in neonates.…”
Section: Accepted For Publication: 17 December 2010mentioning
confidence: 99%
“…Nalbuphine pass through the placenta rapidly[1213] and the elimination half-life of nalbuphine in neonates is 4.1 hours,[14] which was shorter than that of meperidine in neonates 7-32 hours. [15] So, the neonatal effects of nalbuphine will be of shorter duration than meperidine.…”
Section: Discussionmentioning
confidence: 99%
“…[14] to delineate placental transfer and disposition of nalbuphine in the neonate found that nalbuphine placental transfer is high and estimated half life of nalbuphine in neonate is longer than in adult and two neonates had low APGAR score at one minutes and one of them had score of 8, which improved spontaneously to 10 at 5 min and the other had score 3 and improved to 10 after resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Nalbuphine was introduced as a systemic obstetric analgesic in the 1980s, and its safety profile presented also as such an advantage over other opioids that are also known to cross the placental barrier [3,6]. In modern obstetric anesthesia, nalbuphine plays only a neglectable role.…”
Section: Introductionmentioning
confidence: 99%